أثر تكنولوجيا المعلومات في إجراءات رقابة الجودة في مكاتب تدقيق الحسابات في المملكة الأردنية الهاشمية - رزوق, ساطع; عقاب, ريم (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تهدف الدراسة إلى تعرّف أثر تكنولوجيا المعلومات في عناصر رقابة الجودة وإجراءاتها في مكاتب تدقيق الحسـابات، والتي تشتمل (المتطلبات المهنية، إجراءات إدارة الأفراد، عمليات قبول مراجعة العملاء والاستمرار فيها، أداء عملية التدقيق، إجراءات المتابعة والمراقبة في مكاتب تدقيق الحسابات في المملكة الأردنية الهاشمية ) استخدم الباحث المنهج الوصفي التحليلي، بالرجوع إلى أدبيات التدقيق التي تناولت مفهوم رقابة الجودة وإجراءاتها لتعرّف عناصر رقابة الجودة وإجراءاتها ومحاولة بيان أثر تكنولوجيا المعلومات في هذه العناصر والإجراءات، إضافة إلى استطلاع أراء مكاتب تدقيق الحسابات حول أثر تكنولوجيا المعلومات في إجراءات رقابة الجودة التدقيق من خلال الاستبيان الذي تم توزيعه على عينة الدراسة توصلت الدراسة إلى أنه يوجد أثر لتكنولوجيا المعلومات في إجراءات رقابة الجودة في مكاتب تدقيق الحسابات بدرجة كبيرة على عناصر جودة التدقيق التي تشتمل (المتطلبات المهنية، إجراءات إدارة الأفراد،عمليات قبول مراجعة العملاء والاستمرار فيها، أداء عملية التدقيق) وبدرجة متوسطة على إجراءات المتابعة والمراقبة في مكاتب تدقيق الحسابات، حيث ساهمت تكنولوجيا المعلومات في تحقيق أهداف رقابة الجودة. Objectives of the study: The study aims at identifying the impact of information technology on the elements and procedures for quality control in the offices of audit, which includes (professional requirements, procedures for managing people, processes accept and costumer review follow up, the performance of the audit, follow-up action and monitoring in the offices of Audit in Hashemite Kingdom of Jordan). Research Methodology: The researcher uses descriptive method analysis, re-entry to audit literature dealt with the concept and procedures of quality control to identify the elements and procedures for quality control, to describe the impact of information technology on these elements and procedures as well as to explore the views of office audit on the impact of information technology on quality control procedures during the audit of the questionnaire which was distributed to a sample study. The study concluded: information technology has impact on the procedures of quality control in the offices of Audit by a great impact on the elements of quality audit, which includes (professional requirements, procedures for managing people, processes to accept and customers-meeting continuation, the performance of the audit) and a medium degree of follow-up action and surveillance in the offices of the audit, information technology, contributing to the achievement of the objectives of quality control.